Advancing ALS genetics through accessible testing - Fecteau, Teresa (Henry Stewart Talks, 2025)
Current understanding of the genetic basis of ALS, Overview of the ALS Identified genetic testing program, Key findings from the 2024 study analysing program data, The role of genetic counselling and testing in the ALS care journey, How increased access to genetic testing could shape future ALS research and clinical practice